Understanding changes in volatile compounds and fatty acids of Jincheng orange peel oil at different growth stages using GC–MS - Jiao XIE; Qi CAO; Wen-jun WANG; Hong-yan ZHANG; Bing DENG (Journal of Integrative Agriculture)
Jincheng orange (Citrus sinensis Osbeck) is widely grown in Chongqing, China, and is commonly consumed because of its characteristic aroma contributed by the presence of diverse volatile compounds. The changes in aroma during the development and maturation of fruit are indicators for ripening and harvest time. However, the influence of growth stages on the volatile compounds in Jincheng orange remains unclear. In addition, volatiles originate from fatty acids, most of which are the precursors of volatile substances. On this basis, gas chromatography–mass spectrometry (GC–MS) was performed to elaborate the changes in volatile constituents and fatty acids as precursors. This study tested proximately 60 volatiles and 8 fatty acids at 9 growth and development stages (AF1–AF9). Of those compounds, more than 92.00% of total volatiles and 87.50% of fatty acids were terpenoid and saturated fatty acids, respectively. As shown in the PCA plot, the AF5, AF6, and AF9 stages were confirmed as completely segregated and appeared different. In addition, most of the volatiles and fatty acids first increased at the beginning of the development stage, then decreased from the AF6 development stage, and finally increased at the AF9 maturity stage. Moreover, the highest contents of terpenoid, alcohols, aldehydes, ketones, and saturated fatty acids in Jincheng orange peel oil were d-limonene, linalool, octanal, cyclohexanone, and stearic acid during development stages, respectively. Our results found that the growth stages significantly affected the volatile constituents and precursors in Jincheng orange peel oil.